The Hubble Space Telescope UV Legacy Survey of Galactic globular clusters – XXI. Binaries among multiple stellar populations. Issue 4 (31st December 2019) - Milone, A P; Vesperini, E; Marino, A F; Hong, J; van der Marel, R; Anderson, J; Renzini, A; Cordoni, G; Bedin, L R; Bellini, A; Brown, T M; D'Antona, F; et al.
Abstract: A number of scenarios for the formation of multiple populations in globular clusters (GCs) predict that second generation (2G) stars form in a compact and dense subsystem embedded in a more extended first-generation (1G) system. If these scenarios are accurate, a consequence of the denser 2G formation environment is that 2G binaries should be more significantly affected by stellar interactions and disrupted at a larger rate than 1G binaries. The fractions and properties of binary stars can thus provide a dynamical fingerprint of the formation epoch of multiple-population GCs and their subsequent dynamical evolution. We investigate the connection between binaries and multiple populations in five GCs, NGC 288, NGC 6121 (M 4), NGC 6352, NGC 6362, and NGC 6838 (M 71). To do this, we introduce a new method based on the comparison of Hubble Space Telescope observations of binaries in the F275W, F336W, F438W, F606W, and F814W filters with a large number of simulated binaries. In the inner regions probed by our data, we do not find large differences between the local 1G and the 2G binary incidences in four of the studied clusters, the only exception being M 4 where the 1G binary incidence is about three times larger than the 2G incidence. The results found are in general agreement with the results of simulations predicting significant differences in the global 1G and 2G incidences and in the local values in the clusters' outer regions but similar incidences in the inner regions. The significant difference found in M 4 is consistent with simulations with a larger fraction of wider binaries. Our analysis also provides the first evidence of mixed (1G–2G) binaries, a population predicted by numerical simulations to form in a cluster's inner regions as a result of stellar encounters during which one component of a binary is replaced by a star of a different population.